Menopause-related Osteoporosis - Leon C. Snyman (South African Family Practice)
Peak bone mass for spine and hip is reached in the mid-twenties and adolescents should be counselled on adequate nutrition to ensure sufficient calcium intake, regular weight-bearing exercise, maintaining normal body weight, avoiding smoking and limiting alcohol intake. These measures are important to prevent osteopenia and osteoporosis by obtaining a maximum peak bone mineral density (BMD) and to maintain it by avoiding excessive bone loss. One year before the onset of menopause, however, as a result of oestrogen deficiency, there is an increase in osteoclastic activity without a similar increase in osteoblastic activity, resulting in accelerated bone loss. The average decrease in BMD during the menopausal transition is estimated to be about 10% and a woman’s risk of sustaining an osteoporotic or fragility fracture doubles for each decade after the age of fifty. Half of women older than 50 years of age will be osteopenic compared to 10% who are osteoporotic and only 40% will have normal BMD. This article gives an overview of the prevention, diagnosis and management of osteoporosis during and before menopause.